Self-assembly of donor–acceptor conjugated polymers induced by miscible 'poor' solvents. Issue 8 (28th January 2019) - Xi, Yuyin; Wolf, Caitlyn M.; Pozzo, Lilo D.
Abstract : Polarity of 'poor' solvent strongly affects the structure of self-assembled donor–acceptor conjugated polymers. Abstract : The solution-phase self-assembly of donor–acceptor conjugated polymer (DACP) poly[2, 5-(2-octyldodecyl)-3, 6-diketopyrrolopyrrole- alt -5, 5-(2, 5-di(thien-2-yl))thieno[3, 2 b ]thiophene] (DPPDTT), is demonstrated and investigated from binary solvent mixtures. It is found that the polarity of a miscible 'poor' solvent ( e.g. methanol, dimethyl sulfoxide), which is added to a stable polymer solution in chloroform ( i.e. 'good' solvent), strongly affects the resulting nanostructure. Nanoribbons are formed by the addition of certain polar ( e.g. methanol) 'poor' solvents to the mixture, while amorphous aggregates are formed upon addition of non-polar 'poor' solvent, such as n -hexane. Atomic force microscopy (AFM), scanning transmission electron microscopy (sTEM) and small angle neutron scattering (SANS) are used to characterize the shape and size of the nanostructures. Experiments show complex self-assembly in solution occurs for DACPs when compared to conjugated homopolymers. SANS results also provide quantitative analysis of DACP conformations in solution before self-assembly occurs. The addition of different polar 'poor' solvents could also alter the size of the assembled nanostructures, as well as the fraction of polymers that self-assemble. The surface orientation and the crystal structure of the nanostructures is also probed by grazing-incidence wide-angle X-ray scattering (GIWAXS). Organic field effect transistors (OFETs) are used to characterize charge transport properties for nanoribbons where enhancement of the average hole mobility is observed.